2013
DOI: 10.1159/000348850
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Nutrient Intake in Patients with Celiac Disease: Results from a German Dietary Survey

Abstract: Background: Currently, the only treatment for celiac disease (CD) is a lifelong gluten-free diet (GFD). Research has been carried out in various countries into the nutritional adequacy of the GFD in terms of macro- and micronutrients, mostly presenting conflicting results. However, no data for Germany are available to date. Aim: To elucidate the nutritional composition of a GFD and to compare it with non-GFD in a representative German non-CD population. Methods and Patients: A total of 1,000 patients who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 26 publications
6
108
4
2
Order By: Relevance
“…Some studies have suggested that GFD may have an anti-atherosclerotic effect in CD [22][23][24] , whereas others have shown that the diet is likely to be atherogenic [25][26][27] . Serum total cholesterol level was significantly lower in CD compared to healthy controls in our study as reported previously in the adults 22,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that GFD may have an anti-atherosclerotic effect in CD [22][23][24] , whereas others have shown that the diet is likely to be atherogenic [25][26][27] . Serum total cholesterol level was significantly lower in CD compared to healthy controls in our study as reported previously in the adults 22,26 .…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is also present in several studies that refer the GFD to be associated with high protein and lipid intake [32,53,54,55,56]. However, this imbalance cannot be consider only for CD children, since exits a large difference between the nutritional recommendations and the actual consumption of protein reported for general population.…”
Section: Discussionmentioning
confidence: 78%
“…Martin et al [35] analyzed the dietary intake of 88 German patients with CD on the GFD and found suboptimal intake of vitamins B 1 , B 2 , B 6 and folic acid. Similar findings have been published from studies in the US.…”
Section: Micronutrient Imbalances In the Gfdmentioning
confidence: 99%